Comparison of bone age assessments by Gruelich-Pyle, Gilsanz-Ratib, and Tanner Whitehouse methods in healthy Indian children - Nikhil Shah (Wolters Kluwer Medknow Publications, 2021)
Background: There are several methods of bone age (BA) assessment, which include Gruelich-Pyle (GP), Gilsanz-Ratib (GR), and Tanner Whitehouse-3 (TW-3) methods. Although GP atlas is the most widely used, there are concerns about its accuracy in children of different ethnicities, making the use of the TW-3 method an attractive option in Indian children. Objectives: 1) To assess the relationship of BA with chronological age (CA) as assessed by different methods (GP, GR, and TW-3) in healthy Indian children 2) To assess which of the three methods of BA assessment is more suitable in Indian children. Methodology: X-rays of 851 children (438 boys and 413 girls, aged 2–16.5 years) were analyzed by four independent observers using three different methods of BA estimation (GP, GR, and TW-3). Mean BAs were converted to Z-scores. For purpose of deciding which method of BA was most suitable in our cohort, a test of proportions and root mean square (RMS) deviations were computed. Results: Using the test of proportions, the TW-3 method was most suitable overall (P < 0.05). TW-3 method was again most applicable in prepubertal boys (P < 0.05), in prepubertal girls (although not significant, P > 0.1), and pubertal girls (P < 0.05). However, in pubertal boys, the GR atlas method was most suitable (P < 0.05). The same results were obtained when root mean square (RMS) deviations were computed. Interestingly, BA was underestimated in Indian boys irrespective of the method used. In Indian girls, however, the BA was underestimated till the pubertal growth spurt, after which there was rapid advancement of BA. Conclusions: Among the three methods (GP, GR, and TW-3), the BAs estimated by the TW-3 method were closest to CAs. Hence, it seems reasonable to recommend the use of the TW-3 method for BA estimation in the Indian population till an Indian standard bone age atlas is developed.